The aga khan historic cities programme - Jodidio, Philip (New York : Prestel, 2011)
The extraordinary accomplishments of the Aga Khan Historic Cities Programme are celebrated in this generously illustrated volume that includes hundreds of photographs, maps, and drawings along with informative text, offering fascinating insight into the built environment of Muslim societies around the world. The Aga Khan Historic Cities Programme promotes the conservation and re-use of buildings and public spaces in historic cities in the Muslim World as a catalyst to improving the quality of life of their inhabitants. This book presents more than 30 case studies that illustrate the Programme's efforts to spur social, economic, and cultural development in sustainable ways. In countries such as Afghanistan, Egypt, India, Mali, Pakistan, Syria, Tajikistan and Tanzania the Historic Cities Programme has gone beyond restoration to address the questions of the social and environmental context, adaptive re-use, institutional sustainability and training. Recent photographs filled with brilliant detail; precise maps, drawings and technical data; and expert essays on urban planning, collaborative networks, parks and gardens, and sustainability are included in this exciting book on the work of one of the Muslim world's most successful proponents of cultural conservation.
Keywords: Architecture -- Conservation and restoration; Islamic countries; City planning; Sustainable development; Aga Khan Trust for Culture. Historic Cities Support Programme; Historic buildings -- Conservation and restoration